Drag reduction of X-pentamaran ship model with asymmetric-hull outrigger configurations and hull separation - Yanuar; Ibadurrahman Ibadurrahman; A. Gunawan; R. A. Wibowo; Gunawan (Energy Reports, 2020)
The needs to reduce energy consumption have to be applied to all sector, and one of them is transportation. Shipping is the most significant component of it, and therefore optimising a ship performance and reducing its resistance is a subject for many researchers. One of many ways to reduce drag is by utilising an alternative design such as multihull vessel, especially pentamaran, a vessel with five hulls. Destructive interference between their system of waves produced by their hulls is beneficial to reduce power consumption. An experimental test of X-pentamaran model in calm water condition had been conducted to investigate the interference resistance. Wigley hull-form of the model with four asymmetric-hull configurations and three variations of hull separation was investigated. The ship model was towed in a fixed towing condition and calm water condition with Froude number ranging from 0.2 to 0.7. The results showed that the hull separation made a slight alteration of the total resistant coefficient (in magnitude) on the same configuration. Even though not a single configuration outperformed the others in the entire range of Froude number, two configurations with S/L=0.11 showed the highest drag reduction performance as the optimum model based on their Froude number range: configuration A3 from Froude number ranging from the initial to 0.6 and configuration C3 for the rest of the Froude number range.
Keywords: 330; Drag reduction; Asymmetric-hull configuration; Pentamaran; Wigley-hull form; Hull separation